Pengaruh durasi senam diabetes pada penurunan glukosa darah penderita diabetes mellitus tipe II - Weni Kurdanti; Tri Mei Khasana (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: The management of DM focused on four pillars: education, nutrition therapy, physical exercise, and pharmacological interventions. In type 2 diabetes, physical activity functions primarily in controlling diabetes.Objective: This study aims to determine the effect of differences in the duration of aerobic exercise on blood glucose levels.Method: This was quasi-experimental research with pre-post test design. A total of 24 respondents with type 2 diabetes were divided into two groups consisting of groups A that received aerobic exercise with a duration of 30 minutes and group B received aerobic exercise with a duration of 60 minutes for 6 weeks and frequency of exercise 3 times each week. Statistical tests use paired t-tests and independent t-tests.Results: The mean post-test blood sugar level based on HbA1c measurements in group A was 7.92±1.56% while group B was 7.13±0.99%. Mean pre-test - post-test blood sugar levels in the two groups were significantly different (p<0.05). Aerobic exercise for 6 weeks with a frequency of 3 times each week can reduce HbA1c by -2.5±0.96% in group A while group B increased by 0.02±0.29%. There is a significant difference in HbA1c before and after 6 weeks of aerobic exercise between two groups (p=0.021).Conclusion: Aerobic exercise with a duration of 30 minutes for 6 weeks 3 times each week can reduce blood glucose (HbA1c) by -2.5±0.96% while the group duration of aerobic exercise 60 minutes an increase of 0.02±0.29%. There is a significant difference in HbA1c before and after 6 weeks of aerobic exercise between the two groups.